Effect of methomyl on fertility, embryotoxicity and physiological parameters in female rats - Haneia I. Mokhtar, Hasan A. Abdel-Latif, Reda H. ElMazoudy, Wessam M. Abdelwahab, Mona I. Saad. (Journal of Applied Pharmaceutical Science, 2013)
The widespread use of pesticide leads to severe environmental pollution and health hazards. In the present study sexually mature female rats were administered methomyl at three different doses (2 mg/kg b.wt, 1 mg/kg b.wt and 0.67 mg/kg b.wt corresponding to 1/10 and 1/20 and 1/30 LD50 methomyl, respectively) daily by oral gavage for 28 consecutive days. Some biochemical parameters (lipid profiles, total proteins), levels of sex hormones in addition to fertility index and reproductive outcomes were determined. The levels of MDA and the activities of ovarian antioxidant enzymes (CAT, SOD, Gpx) were also estimated. Methomyl exposure increased maternal levels of cholesterol, triglyceride, total lipids, and levels of estradiol; and reduced the levels of progesterone in the 1/10 and 1/20 LD50 groups whereas no changes in total proteins were observed. In addition, methomyl treatment significantly reduced the number of implantation sites, the number of live fetuses and increased the incidence of dead embryos and resorption sites at the same dose levels. The antioxidative status in the ovary at the higher dose of methomyl was markedly depleted. Histopathological examination of the intoxicated ovaries revealed variable degrees of degenerative changes in the 1/10 and 1/20 LD50 groups. In conclusion, exposure of female rats to methomyl induced maternal and developmental toxicity at 1/10 and 1/20 LD50 groups. However, 1/30 LD50 methomyl dose produced no evidence of maternal toxicity. Therefore, its application should be limited to a designed program with special care in handling to minimize its hazards.
Keywords: Resorption, Fertility, Fetus, Implantation, pregnancy, Oxidative stress.